2009
DOI: 10.1016/j.expneurol.2009.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gastric emptying and enteric nervous system dysfunction in the rotenone model of Parkinson's disease

Abstract: Gastrointestinal (GI) dysfunction is the most common non-motor symptom of Parkinson’s disease (PD). Symptoms of GI dysmotility in PD include early satiety and weight loss from delayed gastric emptying and constipation from impaired colonic transit. Understanding the pathophysiology and treatment of these symptoms in PD patients has been hampered by the lack of investigation into GI symptoms and pathology in PD animal models. We report that the parkinsonian neurotoxin and mitochondrial complex I inhibitor roten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
114
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 48 publications
8
114
0
Order By: Relevance
“…The stool water content was then calculated as an indicator of colon water absorption. The results were normalized to body weight (adapted from a method described in Li et al and Greene et al [24,25] www.fhc.viamedica.pl free access to pre-weighed food for sixty minutes. Thirty minutes later, the animals were euthanized via decapitation, and the stomach was excised and weighed, then dried using filter paper after removal of its contents and weighed again.…”
Section: Methodsmentioning
confidence: 99%
“…The stool water content was then calculated as an indicator of colon water absorption. The results were normalized to body weight (adapted from a method described in Li et al and Greene et al [24,25] www.fhc.viamedica.pl free access to pre-weighed food for sixty minutes. Thirty minutes later, the animals were euthanized via decapitation, and the stomach was excised and weighed, then dried using filter paper after removal of its contents and weighed again.…”
Section: Methodsmentioning
confidence: 99%
“…The mean weight of rats in the control group increased throughout the research period; whereas rats in the rotenone group exhibited weight loss in the first 4 weeks, followed by a weight increase until the 12th week and a gradual decrease between weeks 16-24. Rats in the rotenone rat model exhibited obvious weight loss, which was regarded to be associated with the damage to gastrointestinal neurons (13,14), which impede digestion. This symptom of weight loss also manifests in patients with PD (15,16).…”
Section: Rotenone Treatment Induces Behavioral Deficits and Mortalitymentioning
confidence: 99%
“…Indeed, Greene et al [17] reported that rats chronically treated with systemic rotenone, a mitochondrial toxin that replicates PD features in rodents [4], showed a transient decrease in stool frequency and weight loss. Aphagia and weight loss have been described in rotenone-treated animals [4,14] and may play a major role in the decreased stool frequency observed in this model.…”
mentioning
confidence: 99%